2018
DOI: 10.1186/s12937-017-0308-8
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional adequacy of a novel human milk fortifier from donkey milk in feeding preterm infants: study protocol of a randomized controlled clinical trial

Abstract: BackgroundFortification of human milk is a standard practice for feeding very low birth weight infants. However, preterm infants often still experience suboptimal growth and feeding intolerance. New fortification strategies and different commercially available fortifiers have been developed. Commercially available fortifiers are constituted by a blend of ingredients from different sources, including plant oils and bovine milk proteins, thus presenting remarkable differences in the quality of macronutrients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 32 publications
(29 reference statements)
0
32
0
1
Order By: Relevance
“…The recruitment period was 27 November 2014 to 22 December 2016. All the details about the clinical trial have been deeply described in two previous reports [18,20]. The present research was performed in a subpopulation of the original cohort that successfully completed the study period and whose urinary samples at the beginning of fortification (Time 0) and 21 days later (Time 1) were available.…”
Section: Clinical Trial and Interventionmentioning
confidence: 99%
“…The recruitment period was 27 November 2014 to 22 December 2016. All the details about the clinical trial have been deeply described in two previous reports [18,20]. The present research was performed in a subpopulation of the original cohort that successfully completed the study period and whose urinary samples at the beginning of fortification (Time 0) and 21 days later (Time 1) were available.…”
Section: Clinical Trial and Interventionmentioning
confidence: 99%
“…Median value for bradycardia was 67 (63-78) beats per minute with a lowest of 58 beats per minute. The median duration of apnea events was 12 (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) seconds, the longest apnea recorded was 38 seconds long. Detailed CR monitoring data are reported in Table 3.…”
Section: Resultsmentioning
confidence: 97%
“…(14) The evaluation of GER and gastric emptying, as a marker of FI, was evaluated by multichannel intraluminal impedance and pH monitoring (MII/pH) and gastric ultrasound (US) as secondary endpoints of the FortiLat trial. (14,15) Aim of this study is to evaluate the effects of the DF on VLBW and very preterm infants enrolled in the FortiLat trial with symptoms of GER and CR events.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last decade, because of anti-allergenic properties, mainly in infants exhibiting Cow Milk Protein Allergy [52][53][54], donkey milk has received interest as a breast milk substitute, mainly due to its colostrum content. Thus, the study of the β-lactoglobulin, identified in two molecular forms-β-lactoglobulin I, and β-lactoglobulin II-in donkey milk and colostrum, respectively [55].…”
Section: Literature Reviewmentioning
confidence: 99%